The eye exam and basic ophthalmic instruments [ - Alward, Wallace L. M.; Farrell, Thomas A.; Lawrence, Mary Gilbert; Lewis, Richard A. , 1951-; Movaghar, Mansoor; Verdick, Randall E. (Clinical skills DVD series, 2007)
Eye exam : the essentials (c2001): Provides the basic framework for the ocular examination of an adult or a child. Demonstrates how to take a basic ocular history and perform the basic ocular examination. Shows how to recognize many of the signs and symptoms of eye pathology and when to refer patients to an ophthalmologist. Topics covered include: visual acuity testing, the external examination, pupillary examination, ocular motility, and dilated direct ophthalmoscopy